Relation of Superficial and Deep Layers of Delaminated Rotator Cuff Tear to Supraspinatus and Infraspinatus Insertions - Seo, Joongbae (Indian J Orthop, 2020)
BACKGROUND: It remains unclear whether the deep layer of the rotator cuff is an articular layer of the supraspinatus (SS) or infraspinatus (IS), rotator cable, or superior capsule. Therefore, this study aimed to analyse the relationship between occupation ratios and delamination patterns of rotator cuff tears (RCTs). We hypothesised that the deep layers are related to the occupation ratios of the deep SS and IS sections. MATERIALS AND METHODS: A total of 265 patients with RCTs were retrospectively enrolled between 2013 and 2017 and divided into four groups: A, non-delaminated tear; B, delaminated tear with the deep layer equally retracted to the superficial layer; C, delaminated tear with the deep layer more retracted; D, delaminated tear with the superficial layer more retracted. Muscle volume was evaluated by measurement of each occupation ratio of the SS and IS, and the IS muscle was additionally divided into two areas, deep and superficial. RESULTS: The SS occupation ratio was significantly lower in group C than in the other groups (p = 0.009). Conversely, comparison of the IS occupation ratios revealed no significant intergroup differences. The occupation ratio of the superficial IS was significantly lower in group D than in the other groups (p = 0.003). In group C, the occupation ratios of the deep IS section were significantly decreased according to RCT size (p = 0.034). CONCLUSION: Our findings demonstrate that the superficial layers are related to the IS superficial section and the deep layers to the SS and IS deep sections. LEVEL OF STUDY: IV.